Pembelajaran bahasa inggris berbasis permainan edukatif untuk penguasaan kosakata things in the classroom pada siswa sekolah dasar - Helena Badu; Rasuna Rasid Talib (Penamas: Journal of Community Service, 2026)
The mastery of English vocabulary from the elementary school level serves as an important foundation for the development of learners’ future language skills. However, English language instruction in elementary schools often faces challenges, particularly low student learning motivation and limited variation in teaching methods. This community service activity aimed to introduce English language learning through educational games using the topic Things in the Classroom for fourth-grade students at SDN 12 Kota Barat. The activity was conducted on December 9, 2025, involving eight students and implemented through the preparation, implementation, and evaluation stages. The instructional approach employed was educational game-based English learning (game-based learning), which was implemented through a contextual vocabulary introduction strategy and learning techniques in the form of Simon Says and song with movement activities using simple rhythmic chants. The results indicated that the game-based learning approach created an active and enjoyable learning atmosphere, increased student engagement, and supported the meaningful acquisition of basic English vocabulary. In addition to its positive impact on students, the activity also provided pedagogical experience for university students and inspired creative teaching practices among classroom teachers. Therefore, educational game-based English learning has the potential to be sustainably implemented in elementary school instruction.